Irigasi Kecil: Kinerja, Masalah, dan Solusinya - Tri Bastuti Purwantini; Rita Nur Suhaeti (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2017)
Irrigation facilities is one of the key factors in farming, especially for food crop farming, including rice. A small-scale irrigation system has an area of less than 500 hectares, and it is the backbone of family food security which in turn will lead to national food security. Damage irrigation system networks will threaten food production increase. In the future, irrigation infrastructure must be better managed so that agricultural sector can realize agricultural diversification, conserve wider irrigation system and maintain local wisdom and social capital in irrigation management. The objective of the paper is to analyze performance, problems and solutions of small irrigation systems in Indonesia, including small irrigation concepts and understanding, small irrigation performance and development, small irrigation development policies, factors affecting smallscale irrigation development, investments, and prospects. The paper also compares various performances, problems and solutions of small irrigation systems in other countries. Small scale irrigation performance is often better than large-scale irrigation, in the sense of water availability throughout the year and equitable water distribution for all service areas. AbstrakSarana irigasi merupakan faktor penting dalam usaha tani khususnya tanaman pangan. Sistem irigasi kecil dengan luas oncoran kurang dari 500 ha merupakan tulang punggung ketahanan pangan keluarga yang pada gilirannya bermuara pada ketahanan pangan tingkat nasional. Kerusakan jaringan sistem irigasi akan mengancam peningkatan produksi pangan. Di masa yang akan datang, infrastruktur irigasi harus dikelola secara lebih baik agar sektor pertanian dapat mewujudkan diversifikasi pertanian, semakin luasnya konservasi sistem irigasi, serta kearifan lokal dan modal sosial dalam pengelolaan irigasi dapat terpelihara. Tulisan ini bertujuan menganalisis kinerja, masalah dan solusi sistem irigasi kecil di Indonesia, termasuk konsep dan pengertian irigasi kecil, kinerja dan perkembangan irigasi kecil, kebijakan pengembangan irigasi kecil, faktor-faktor yang mempengaruhi pengembangan investasi irigasi kecil, dan prospek pengembangan irigasi kecil. Dalam tulisan ini juga dibandingkan berbagai kinerja, masalah dan solusi dari sistem irigasi kecil di negera-negara lain. Kinerja irigasi kecil seringkali lebih baik dari irigasi skala besar, dalam arti ketersediaan air sepanjang tahun dan terdapat keadilan pembagian air untuk seluruh wilayah oncorannya.